Preventing food allergy in infancy and childhood: Systematic review of randomised controlled trials. Issue 7 (18th June 2020) - de Silva, Debra; Halken, Susanne; Singh, Chris; Muraro, Antonella; Angier, Elizabeth; Arasi, Stefania; Arshad, Hasan; Beyer, Kirsten; Boyle, Robert; du Toit, George; Eigenmann, Philippe; Grimshaw, Kate; et al.
Abstract: Background: This systematic review of ways to prevent immediate‐onset/IgE‐mediated food allergy will inform guidelines by the European Academy of Allergy and Immunology (EAACI). Methods: The GRADE approach was used. Eleven databases were searched from 1946 to October 2019 for randomized controlled trials (and large prospective cohort studies in the case of breastfeeding). The studies included heterogeneous interventions, populations, and outcomes and so were summarized narratively. Results: Forty‐six studies examined interventions to reduce the risk of food allergy in infancy (up to 1 year) or early childhood. The following interventions for pregnant or breastfeeding women and/or infants may have little to no effect on preventing food allergy, but the evidence is very uncertain: dietary avoidance of food allergens, vitamin supplements, fish oil, probiotics, prebiotics, synbiotics, and emollients. Breastfeeding, hydrolyzed formulas, and avoiding cow's milk formula may not reduce the risk of cow's milk protein allergy; however, temporary supplementation with cow's milk formula in the first week of life may increase the risk of cow's milk allergy. Introducing well‐cooked egg, but not pasteurized raw egg, from 4 to 6 months probably reduces the risk of hen's egg allergy. Introducing regular peanut consumption into the diet of an infant at increased risk beginning from 4 to 11 months probably results in a large reduction in peanut allergy in countries with a high prevalence. These conclusions about introducing peanut are based on moderate certainty evidence, from single trials in high‐income countries. Conclusions: Sixty percent of the included studies were published in the last 10 years, but much still remains to be understood about preventing food allergy. In particular, there is a need to validate the potential benefits of early introduction of food allergens in a wider range of populations. Abstract :